2016
DOI: 10.1182/blood-2015-07-657056
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α regulates the interaction of chronic lymphocytic leukemia cells with the tumor microenvironment

Abstract: Key Points HIF-1α critically regulates the interaction of neoplastic CLL cells with the leukemic microenvironment. HIF-1α is regulated at the transcriptional level in CLL patients and correlates with CXCR4 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 44 publications
6
59
0
Order By: Relevance
“…18,19 Although circulating CLL cells constitutively express a transcriptionally active HIF-1a, 20 its role in regulating CLL survival and its mechanisms of action remain incompletely understood. 21 This work is based on data indicating that adenosine and hypoxia collaborate in modifying the tumor microenvironment in a protolerogenic and tumor-supportive way. 22,23 Here, we show that CLL cells hosted in proliferation centers of LNs overexpress functional HIF-1a.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Although circulating CLL cells constitutively express a transcriptionally active HIF-1a, 20 its role in regulating CLL survival and its mechanisms of action remain incompletely understood. 21 This work is based on data indicating that adenosine and hypoxia collaborate in modifying the tumor microenvironment in a protolerogenic and tumor-supportive way. 22,23 Here, we show that CLL cells hosted in proliferation centers of LNs overexpress functional HIF-1a.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that HIF-1α induces an upregulation of chemokine receptors, such as CXCR4, and cell adhesion molecules that control the interaction of leukemic cells with bone marrow (BM) and lymphoid microenvironments. 9 In line with this, inactivation of HIF-1α was shown to impair chemotaxis and cell adhesion to stroma, reduce BM and spleen colonization in xenograft and allograft CLL mouse models, and prolong survival of these mice. In support of a modulation of CLL cell motility, HIF-1α transcript levels were shown to correlate with the expression of CXCR4 and other target genes in CLL patient samples.…”
mentioning
confidence: 75%
“…In the current study, we explored the effects of IBL‐202 against CLL cells under conditions that mimic the tumour microenvironment. Given the growing body of evidence suggesting CLL cells may adapt to, survive and even proliferate under hypoxic conditions (Shachar et al , ; Koczula et al , ; Valsecchi et al , ) and that activity of the PIM kinases is oxygen‐sensitive (Chen et al , 2009a; Warfel et al , ), we assessed the effects of IBL‐202 under in vitro conditions which are believed to more accurately represent those experienced by CLL cells in the lymph node and marrow (Herishanu et al , ). The significant decrease in the spontaneous apoptosis rate of primary CLL cells (Fig A) and the continued proliferation (albeit at a slower rate) of the OSU‐CLL cell line (Fig B) under hypoxic conditions are consistent with the notion that hypoxia may play a role in the survival of CLL cells in vivo and that CLL cells can adapt to and proliferate even under reduced oxygen tensions.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of CLL cells with stromal cells within these tissues confers resistance to a variety of drugs, including fludarabine (Kurtova et al , ) and ABT‐737 (Vogler et al , ). It is becoming increasingly apparent that hypoxia may also play a significant role in the CLL tumour microenvironment (Huelsemann et al , ; Koczula et al , ; Valsecchi et al , ). A recent study showed that areas within the bone marrow are profoundly hypoxic (Spencer et al , ), suggesting that in order for CLL cells to populate these tissue regions they must have the capacity to adapt to and proliferate under low oxygen tensions.…”
mentioning
confidence: 99%